Attached beyond death: Wild female western lowland gorilla (Gorilla gorilla gorilla) carries and cares for mummified infant - Stephan, Claudia (African Journal of Ecology, 2019)
Nonhuman primate mothers occasionally continue to carry their deceased infants from a few days up to several weeks, and behavioural responses towards the corpse vary (e.g. Watson & Matsuzawa, 2018). General interest in the dead body by other group members is often high (e.g. in chimpanzees, Pan ssp.: Biro et al., 2010; Cronin, Van Leeuwen, Mulenga, & Bodamer, 2011) and individuals sometimes show aggressive behaviour towards the corpse and/or cannibalism (De Marco, Cozzolino, & Thierry, 2018; Hosaka, Matsumoto-Oda, Huffman, & Kawanaka, 2000; Nishida, 1998). Nonhuman primate mothers often continue to groom infants (e.g. in mountain gorillas, Gorilla beringei beringei: Warren & Williamson, 2004; ring-tailed lemurs, Lemur catta: Nakamichi, Koyama, & Jolly, 1996) but dead bodies are mainly transported one-handed or in the mouth, very differently than live infants (e.g. Kooriyama, 2009). This suggests that bodies are perceived differently than infants that are alive. Several factors seem to impact on the interaction with corpses but their exact nature and how they might interact with each other widely remains nebulous (e.g. oxytocin based mother–infant bonds: Bercovitch, 2019; weather conditions decreasing decomposition rate: Haglund & Sorg, 1997; learning infant handling: Warren & Williamson, 2004; and animacy detection malfunctions: Gonçalves & Biro, 2018). Systematic observations of behaviour directed towards deceased infants are thus crucial to better understand the wide-spread interactions with dead conspecifics in the animal kingdom, which seem to be especially promoted in highly social species (e.g. Anderson, 2016; Gonçalves & Carvalho, 2019). While several observations of behaviours towards dead conspecifics are available for chimpanzees, reports on other great ape species are less frequent. Comparative observations in great apes and other nonhuman primates could reveal whether humans are unique in our ‘culturised’ ways to grieve (Huntington & Metcalf, 1979; Shimane, 2018). To the best of my knowledge, the present report is the first to provide observations on a wild, female western lowland gorilla (Gorilla gorilla gorilla), who was observed to carry her dead infant for at least 16 days. Observations presented here include responses of other group members to the female and her dead offspring.<br